2019
DOI: 10.2147/jaa.s150251
|View full text |Cite
|
Sign up to set email alerts
|

<p>Iodixanol nasal solution reduces allergic rhinoconjunctivitis signs and symptoms in Allergen BioCube<sup>&reg;</sup>:&nbsp;a randomized clinical trial</p>

Abstract: Purpose Allergic rhinitis (AR) affects ~20% of the population worldwide. The objectives of this study were to evaluate the safety and efficacy of iodixanol nasal solution (Nasapaque) for AR treatment, using the Allergen BioCube ® (ABC ® ), an environmental exposure unit. Iodixanol is a commonly used contrast media agent that shows efficacy on the signs and symptoms of AR. Patients and methods Seventy-three adult subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In this respect, numerous clinical trials have been conducted using parallel‐group or cross‐over designs in order to test the efficacy of drugs with prophylactic therapeutic potential, such as INCS, 1485–1489 or with immediate therapeutic activity, such as antihistamines 1490–1496 . Novel anti‐inflammatory compounds, 1497–1501 drug‐free nasal fluids, 1502,1503 and probiotics 1504,1505 have also been tested by this method. Additionally, the efficacy of AIT 1506–1517 and air cleaners 1518,1519 has been tested, as well as the influence of allergic nasal symptoms on the absorption of nasally applied drugs 1520 .…”
Section: Evaluation and Diagnosismentioning
confidence: 99%
“…In this respect, numerous clinical trials have been conducted using parallel‐group or cross‐over designs in order to test the efficacy of drugs with prophylactic therapeutic potential, such as INCS, 1485–1489 or with immediate therapeutic activity, such as antihistamines 1490–1496 . Novel anti‐inflammatory compounds, 1497–1501 drug‐free nasal fluids, 1502,1503 and probiotics 1504,1505 have also been tested by this method. Additionally, the efficacy of AIT 1506–1517 and air cleaners 1518,1519 has been tested, as well as the influence of allergic nasal symptoms on the absorption of nasally applied drugs 1520 .…”
Section: Evaluation and Diagnosismentioning
confidence: 99%
“…Studies comparing the effect of Iodixanol to other iodinated contrast media showed similar or less adverse reactions [29,31,32]. Iodixanol can be applied as an active material of Visipaque in the therapeutic treatment of allergic rhinoconjunctivitis [33]. It can also contribute to the higher purity and longer lifetime of human islet cultures [34].…”
Section: Introductionmentioning
confidence: 97%